Contemporary issues in financial reporting : a user-orientated approach - Rosenfield, Paul. (New York : Routledge, 2006)
The book provides information and analysis on all issues to help towards the needsof the users of financial reports.
Includes bibliographical references and index.
aia 07/05/13
Loan
Keywords: Financial statements; Financial reporting